Concentrations of potentially toxic metals and trace elements in pregnant women and association with birth outcomes: A cross-sectional study in Malawi. - Mphatso Mwapasa; Shanshan Xu; Bertha Magreta Chakhame; Alfred Maluwa; Halina Röllin; Augustine Choko; Sandra Huber; Jon Øyvind Odland (Public Library of Science (PLoS), 2024)
Potentially toxic metals and trace elements have been used in Malawi for a long time. However, data on exposure to these elements by susceptible groups like pregnant women and its associations with reproductive health outcomes in Malawi and southern hemisphere is limited. We investigated the concentrations of potentially toxic metals as well as trace elements in pregnant women and assessed the relationship between the levels these elements in maternal blood and sociodemographic factors, dietary habits and birth outcomes. Maternal data was collected from 605 pregnant women. Provider administered questionnaire was used to collect data on maternal sociodemographic factors, life style and immediate birth outcomes. Maternal venous blood samples were collected from 506 pregnant women in southern Malawi between August 2020 and July 2021. An inductively coupled plasma mass spectrometry (ICP-MS) technique was used to analyse maternal blood samples for concentrations of arsenic (As), copper (Cu), lead (Pb), mercury (Hg), nickel (Ni), selenium (Se) and zinc (Zn). Maternal age emerged as the primary predictor for Cu (p = 0.023), As (p = 0.034) and Hg (p = 0.013) blood concentrations, followed by area of residence, which had significant impact on Ni (p = 0.024) and As (p < 0.001) concentrations. High maternal blood concentrations of Ni were associated with increased birth weight (p = 0.047), birth length (p = 0.026), head circumference (p = 0.029) and gestational age (p = 0.035). Negative associations were observed between maternal whole blood total arsenic (combining organic and inorganic As) concentration and neonatal birth length (p = 0.048) and head circumferences (p < 0.001). Similarly, higher maternal blood Pb concentrations were associated with smaller head circumference (p = 0.002) and birth weight (p = 0.016). This study demonstrates the need to introduce biomonitoring studies in Malawi and countries with similar settings in the global south.